2016
DOI: 10.1061/(asce)co.1943-7862.0001126
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Value of 4D Visualizations for Enhancing Mindfulness in Utility Reconstruction Works

Abstract: This paper reports on an ethnographic-action research study of four-dimensional (4D) based coordination in three utility reconstruction projects. This research shows that implementation of 4D models in planning meetings supports mindful behavior, making stakeholders: (1) sensitive to operational processes, (2) pre-occupied with errors and inaccuracies, (3) resistant to simplifying construction plans, and (4) resilient and aware of process alternatives. By being first in synthesizing 4D implementation and mindf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The results revealed that ethnographic research contributed to a variety of areas within the field of construction management. Ethnographic work provided insights on complex social phenomenon such as protests (Teo & Loosemore, 2014) and compensation cultures (Oswald et al, 2019a); into the complexities associated with the implementation of new technology (Scholtenhuis et al, 2016); as well as insights into social classes (e.g. Thiel, 2012) and practices (Mäki & Kerosuo, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results revealed that ethnographic research contributed to a variety of areas within the field of construction management. Ethnographic work provided insights on complex social phenomenon such as protests (Teo & Loosemore, 2014) and compensation cultures (Oswald et al, 2019a); into the complexities associated with the implementation of new technology (Scholtenhuis et al, 2016); as well as insights into social classes (e.g. Thiel, 2012) and practices (Mäki & Kerosuo, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Ethnographic-action research has been a popular choice for investigating technology on construction projects. Scholtenhuis et al (2016) implemented 4D models on three case projects, before qualitatively assessing them in an ethnographic-action research approach. Project meetings were tape recorded and notes were taken about how the 4D-models influenced mindful behaviour.…”
Section: Alternate Applied Forms Of Ethnographic Research [Insert Table 4]mentioning
confidence: 99%
See 3 more Smart Citations